The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fnmol.2017.00307
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Ethanol during Adolescence Leads to Lasting Behavioral Changes in Adulthood and Alters Gene Expression and Histone Methylation in the PFC

Abstract: Adolescents primarily consume alcohol in binges, which can be particularly harmful to the developing frontal cortex and increase risk for an adult alcohol use disorder. We conducted a study investigating immediate and long lasting changes to the prefrontal cortex (PFC) transcriptome to determine the molecular mechanisms underlying adult ethanol behavioral sensitivity following binge ethanol in adolescence. DBA/2J mice were orally dosed with 4 g/kg ethanol intermittently from day 29 to 42. Adolescent mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 79 publications
(126 reference statements)
6
51
1
Order By: Relevance
“…Repeated ethanol administration (2.0-4.0 g/kg, once daily for a total of 7-8 administrations) has been shown to impair cognitive performance in the NOR test in rats (Marszalek-Grabska et al, 2018) and in mice (Wolstenholme et al, 2017). Moreover, Marco et al (2017) reported performance deficits in the NOR test, in male and female Wistar rats that selfadministered ethanol (20% in drinking water) four times a week during PDs 28-52.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated ethanol administration (2.0-4.0 g/kg, once daily for a total of 7-8 administrations) has been shown to impair cognitive performance in the NOR test in rats (Marszalek-Grabska et al, 2018) and in mice (Wolstenholme et al, 2017). Moreover, Marco et al (2017) reported performance deficits in the NOR test, in male and female Wistar rats that selfadministered ethanol (20% in drinking water) four times a week during PDs 28-52.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using genomic profiling of transcripts in the PFC, a recent study showed that binge EtOH reduced myelin‐related gene expression and altered chromatin modifying genes involved in histone demethylation at H3K9 and H3K36. Thus, EtOH may regulate histone methylation as a switch for regulation of myelin . These are the potential pathways that EtOH exposure during critical periods of development can have long‐lasting effects on neurobehavioral function and could, in part, explain the deficits noted in FASDs, as well as persistent cognitive and behavioral problems related to adolescent binge alcohol exposure.…”
Section: Etoh Impacts the Development Of Olsmentioning
confidence: 99%
“…We used the novel object recognition task to measure prefrontal cortex (PFC)-mediated recognition memory, as previously described [30]. Novel object recognition involved a training and a test phase, separated by a 5-min delay.…”
Section: Novel Object Recognitionmentioning
confidence: 99%
“…The light-dark (LD) box conflict model for anxiety-like behavior was conducted using a standard commercial open field activity box divided into two equally sized light and dark zones (25.4 × 12.7 × 20.3 cm). Tracking software (Fusion v5.3; Omnitech Electronics Inc.) was used to record movement, as described [30]. Animal position and locomotor activity was monitored by infrared photobeam breaks.…”
Section: Anxiety-like Behavior In the Light-dark Boxmentioning
confidence: 99%